Global Financial Stability Report, April 2022. (Global Financial Stability Report; Global Financial Stability Report, 2022)
Chapter 1 looks at the implications of the war in Ukraine on the financial system. Commodity prices pose challenging trade-offs for central banks. Many emerging and frontier markets are facing especially difficult conditions. In China, financial vulnerabilities remain elevated amid ongoing stress in the property sector and new COVID-19 outbreaks. Central banks should act decisively to prevent inflation from becoming entrenched without jeopardizing the recovery. Policymakers will need to confront the structural issues brought to the fore by the war, including the trade-off between energy security and climate transition. Chapter 2 discusses the sovereign-bank nexus in emerging markets. Bank holdings of domestic sovereign bonds have surged in emerging markets during the pandemic. With public debt at historically high levels and the sovereign credit outlook deteriorating, there is a risk of a negative feedback loop that could threaten macro-financial stability. Chapter 3 examines the challenges to financial stability posed by the rapid rise of risky business segments in fintech. Policies that target both fintech firms and incumbent banks proportionately are needed.